The E-internal audit iso 9001:2008 based on accreditation form assessment matrix in study program for effectiveness of monitoring accreditation - Marzuki Marzuki; Maria Shusanti Febrianti (International Conference on Engineering and Technology Development (ICETD), 2013)
Accreditation is one of the form external quality guarantee system, it is a process that used in authorized institution in giving formal recognition that an institution has an ability to do certain activity. On the pepare processing there is some things that should be done by study program by using internal audit in periodic time. Internal audit is an independence activity, objectivity, and consultative which is designed to increase the organization’s operation This scientific Writing will specifically focus on internal process audits in preparation for accreditation of Information Engineering Study Program at Bandar Lampung University  with doing  monitoring directly that can be accessed by some units in a management system based on guidelines and standards for internal audit issued by one of several organizations ISO, the quality management system ISO 9001: 2008,  one of the requirements that must be fulfilled conduct periodic internal audits. This standard is very good when applied in the preparation of the accreditation process, accreditation assessment matrix as a guide in conducting internal audits.